Emotion and Imitation: The Jesus Figure in Erasmus's Gospel Paraphrases. Issue 2 (3rd July 2017) - Leushuis, Reinier
Abstract : The Jesus figure poses a challenge for Erasmus in his Paraphrases on the New Testament (1517–1524): how to develop a character whose eschatological foreknowledge prevents him from playing a human, participatory role in the gospel narrative? Erasmus partly compensates this lack of agency with rhetorical accommodatio, emphasizing the adaptive gradualness by which Jesus teaches the exegetical meaning of events and miracles to other biblical characters. Yet in doing so, Erasmus instrumentalizes emotion well beyond oratorical movere, allowing us to re-appreciate Jesus as a literary character. After a brief analysis of the Disputatiuncula de taedio, pavore, tristicia Iesu (1503), which evinces Erasmus's understanding of the role of emotions in the scriptural Jesus, my essay focuses on the affective interactions between Jesus and his disciples in various episodes from the gospel paraphrases. I argue that Erasmus's paraphrastic text grants a key role to the emotions in the transmission of faith and gospel wisdom to the minds of the disciples, and, mimetically, to the sphere of thought and action of the reader and the imagined listeners in the homiletic community.